Diagnosis of peptic ulcer in general practice: an analysis of 183 cases of gastro-intestinal ulceration with particular reference to the Gregersen Benzidine Slide Test - Lipetz, Samuel (The University of Edinburgh, 1947)
1. For many years I have been using the Gregersen Benzidine Slide Test as an aid to the diagnosis of alimentary neoplasm and peptic ulcer 2. An account of its history and evolution is given, with a review of the published opinion of the various well-known workers concerning its reliability as an aid in the diagnosis and treatment of gastro-intestinal disease. 3. The technique of the test and the preparation of the patient¡ are described. 4. It has generally been found that the great majority of cases of active peptic ulcer and alimentary neoplasm excrete occult blood in the faeces and give a positive result with the Gregersen Slide Test. 5. 183 case histories are given. These include 132 cases of duodenal ulcer; 24.cases of gastric ulcer; 13 cases of neoplasm; 8 cases of diverticulitis and 8 other miscellaneous conditions. 6. In the majority of these cases the Gregersen Slide Test or an X -ray investigation, or both, were performed. 7. A statistical analysis has been made of these cases, with special reference to the reliability of the Gregersen Slide Test in comparison with X-ray examination and clinical signs and symptoms. 8. The Gregersen Slide Test is found to be positive in about 88 per cent. of cases, and also gives a positive result in about 18 per cent. of cases clinically confirmed, for which the X -ray findings were negative. 9. The yearly incidence of peptic ulcers, perforated and non-perforated, in the present series of cases is compared with already published findings. 10. These show that there is some indication of a rise in the incidence of perforated and non- perforated ulcers during the war period. 11. The association of certain other pathological conditions is noted, and their significance in the etiology of peptic ulcer is discussed. 12. Emphasis is laid on the ease and rapidity with which the Gregersen Slide Test can be performed in general practice. 13. The opinion is expressed that in cases with symptoms of persisting alimentary dysfunction its application is as important as are the tests for sugar and albumin in suspected cases of diabetes and nephritis.
The diagnosis of peptic ulcer in general practice: an analysis of 183 cases of gastro-intestinal ulceration with particular reference to the Gregersen Benzidine Slide Test